Demographic Controversies and Green Buying Intention: The Moderating Effects of Gender, Age, Income and Education - Yada, Abera Legesse; Kumar, Satinder (The journal of contemporary issues in business and government, 2021)
A lot has been debated on the inconsistent empirical results of green customers’ personal profiles. The inconsistence results among writers created difficulty in finding the right market segment to green products.To examine this discrepancy, a total of 402 academic staffs from universities in Addis Ababa, Ethiopiawere randomly approached. Data was examinedusing multiple regression analysis method.The finding revealed that personal norm, perceived consumer effectiveness, attitude towards green behavior and trust in green products significantly predictsintention and income, gender, education and age plays significant moderating role between limitedpsychometric factors andintention. The result also exhibited that male, younger, lower income earners and educated consumers are greener.